2003
DOI: 10.1021/jp0350363
|View full text |Cite
|
Sign up to set email alerts
|

Novel Enolic Surface Species Formed during Partial Oxidation of CH3CHO, C2H5OH, and C3H6 on Ag/Al2O3:  An in Situ DRIFTS Study

Abstract: In situ DRIFTS was used to investigate the formation and reactivity of surface species on Ag/Al2O3 during partial oxidation of CH3CHO, C2H5OH, and C3H6. The exposure of Ag/Al2O3 to CH3CHO/C2H5OH/C3H6 + O2 in a steady state leads to the formation of two kinds of partial oxidation products:  acetate and a novel enolic surface species. Peaks at 1633, 1416, and 1336 cm-1 are assigned to an adsorbed enolic species. The adsorbed enolic species is more prone to react with NO + O2 on Ag/Al2O3 than acetate is, and play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(120 citation statements)
references
References 18 publications
5
114
0
Order By: Relevance
“…In recent studies, relatively durable and inexpensive alumina-supported silver catalysts (Ag/Al 2 O 3 ) have been considered to be a promising candidate for practical usage in the HC-SCR of NO x [2][3][4][5][6][7][8]. In our research into the HC-SCR of NO x over Ag/ Al 2 O 3 , we found a novel enolic surface species on Ag/ Al 2 O 3 [9] and proposed a new mechanism to explain the high-level efficiency of the SCR of NO x by ethanol over Ag/Al 2 O 3 [7,9,10], as shown in Scheme 1. The reaction starts with the formation of nitrates adsorbed on Al 2 O 3 via NO oxidation by O 2 , and enolic species and acetate adsorbed on Ag and Al 2 O 3 via the partial oxidation of C 2 H 5 OH on Ag/Al 2 O 3 [7].…”
Section: Introductionmentioning
confidence: 68%
“…In recent studies, relatively durable and inexpensive alumina-supported silver catalysts (Ag/Al 2 O 3 ) have been considered to be a promising candidate for practical usage in the HC-SCR of NO x [2][3][4][5][6][7][8]. In our research into the HC-SCR of NO x over Ag/ Al 2 O 3 , we found a novel enolic surface species on Ag/ Al 2 O 3 [9] and proposed a new mechanism to explain the high-level efficiency of the SCR of NO x by ethanol over Ag/Al 2 O 3 [7,9,10], as shown in Scheme 1. The reaction starts with the formation of nitrates adsorbed on Al 2 O 3 via NO oxidation by O 2 , and enolic species and acetate adsorbed on Ag and Al 2 O 3 via the partial oxidation of C 2 H 5 OH on Ag/Al 2 O 3 [7].…”
Section: Introductionmentioning
confidence: 68%
“…An Ag/Al 2 O 3 catalyst (Ag loading is 5.0 wt.%) was prepared by an impregnation method as described in our earlier paper [12]. In situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) spectra were recorded on a Nexus 670 (Thermo Nicolet) FT-IR, equipped with an in situ diffuse reflection chamber and a high sensitivity MCT detector.…”
Section: Methodsmentioning
confidence: 99%
“…diesel and lean-burn engines) [5][6][7][8]. The mechanism of HC-SCR of NO in the presence of excess oxygen over Ag/Al 2 O 3 has been proposed as [9][10][11][12][13][14][15][16] …”
Section: Introductionmentioning
confidence: 99%
“…[175][176][177] On a detailed mechanistic level, the role of silver species in the HC-SCR of NO x over Ag/Al 2 O 3 was mainly attributed to enhancement of the partial oxidation of reductants to form active intermediates, and their further reaction to produce N 2 . 16,158,172,178 In situ DRIFTS spectra showed that the surface species formed from the partial oxidation of ethanol over Ag/Al 2 O 3 ( Fig. 3C) were closely related to Ag loading.…”
Section: Partial Oxidation Of Oxygenated Hydrocarbons Over Ag/al 2 Omentioning
confidence: 99%
“…In our earlier papers, 162,172,173 the formation and dynamic performance of partial oxidation products of ethanol over Ag/Al 2 O 3 were studied by an in situ DRIFTS method, and we found a novel enolic species originating from the partial oxidation of ethanol, with the structural feature of an oxygen atom adjacent to carbon-carbon double bonds (CQC-O). As shown in Fig.…”
Section: Partial Oxidation Of Oxygenated Hydrocarbons Over Ag/al 2 Omentioning
confidence: 99%